A Study of Complications following Self-administration with Medical Abortion Pills - Giri, A; Srivastav, VR; Suwal, A; Sharma, B (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: The objective of this study was to find out the complications following self-administration with medical abortion pills. Methods: A prospective descriptive study was conducted in Department of Obstetrics and Gynecology,Nepal Medical College over a period of two years from January 2013 to December 2014 among 48 women who were admitted with abortion complications and also gave history of self-administration of abortion pills. Results: During the study period, 48 women with history of self-medication with abortion pills were admitted with various abortion complications. There were 60% of women who had consumed abortion pills within approved nine weeks gestation while 19% had consumed after nine weeks and 21% after twelve weeks. Majority (60%) were admitted with incomplete abortion, 4% with missed abortion, 13% with continued live pregnancy, 6.5% with septic abortion and 6.5% with ectopic pregnancy. Anemia was present in 79% of patient. More than one third of the patient had severe anemia and blood transfusion was needed in 52%. Surgical evacuation was required in 71% of patient; medical abortion with repeat doses of mifepristone and misoprostol was done in was done 13% and 6.5% needed laparotomy for ectopic pregnancy. Conclusions: Though medical abortion is considered to be highly effective and safe procedure, unsupervised selfadministration of medical abortion pills was associated with serious maternal morbidities. There should be some policy to restrict over the counter sale of this medicine.